The Influence of E-Service Quality on Improving the Performance of The UKT Information System Mediated by Perceived Ease of Use at Palangka Raya University - Tahasak; Rinto Alexandro (International Journal of Contemporary Sciences (IJCS), 2024)
Research in the field of marketing management that leads to practices and policies in technology-based service systems in improving performance. Transparency in payment of educational fees and information is very important with digital information systems. The research was conducted at Palangka Raya University, Central Kalimantan Province, Indonesia. The role of perceived ease of use is also very supportive for people to obtain and use educational fee payment applications. This type of quantitative research uses a questionnaire of 100 respondents in the community who have used e-services, and analyzed using SEM PLS 4.0. The research results show the significant performance of a single tuition information system as information in paying education and fees. Furthermore, the results show that it is very important to manage information systems with a perceived ease of use digital policy. So the implications of these results are to improve information system performance by increasing e-service quality and perceived ease of use at universities